Deconstructing the standpoint of female ex-convicts represented in the TV series Dapur Napi - Sriharyani, Yuni (ProTVF, 2024)
Background: The representation of female ex-convicts, particularly in Indonesia, remains biased despite the increasing number of ex-convict narratives. This study focuses on addressing this gap by examining the TV series “Dapur Napi” on Vidio, exploring how the series illustrates power disparities in the reintegration of female ex-convicts into society and how the series uses hyperbolic dramatization of female ex-convicts for entertainment purposes. Purpose: This research aims to critically analyze how societal power discrepancies are represented in the media and how media constructs the identity and reality of female ex-convicts in “Dapur Napi” through the lens of standpoint theory. Methods: Employing Critical Discourse Analysis by Norman Fairclough, this research dissects the textual, discursive practice, and sociocultural practice dimensions of the TV series using a qualitative approach. Results: The study’s results reveal the portrayal of female ex-convicts, emphasizing complexities in identity construction, societal rejection, and the dual role of media in both entertainment and norm reinforcement. Implications: This research can further develop the discussion on Standpoint Theory, particularly providing insights into inequalities in the representation of marginalized female ex-convicts in popular media. Practically, this research can advocate for more accurate and diverse portrayals, and promote media literacy to challenge stereotypes and promote social inclusion.